Utilization of the physicomimetics framework for achieving local, decentralized, and emergent behavior in a swarm of quadrotor unmanned aerial vehicles (QUAV) - Nakano, Reiichiro Christian S. (Animo Repository, 2017)
This paper presents the implementation of the physicomimetics framework in governing the behavior of a swarm of quadrotors. Each quadrotor uses only local information about itself and the neighboring quadrotors to determine its own movement by applying the principles of physicomimetics. Through these localized and relatively simple interactions, the swarm of quadrotors was able to organize itself into various structures and exhibit different swarm behaviors such as aggregation, obstacle avoidance, lattice formation, and dispersion.